2012
DOI: 10.1364/ome.2.000740
|View full text |Cite
|
Sign up to set email alerts
|

Blue-green luminescent silicon nanocrystals fabricated by nanosecond pulsed laser ablation in dimethyl sulfoxide

Abstract: In this work, stable blue-green luminescent colloidal silicon nanocrystals (SiNCs) are fabricated by nanosecond pulsed laser ablation of a silicon target in dimethyl sulfoxide (DMSO). Transmission electron microscopy and X-ray diffraction analysis have shown the formation of spherical silicon nanocrystals in the colloid with size range of 2-5 nm. Our results show that the DMSO stabilizes the silicon nanocrystals via oxide formations on the nanocrytals surfaces by a simple route of laser ablation and a schemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 35 publications
4
26
0
Order By: Relevance
“…1c) is significantly different from the as-ablated Si NPs (Fig. 17,23,37,38 The PL of the separated Si NPs, centred at 335 nm (3.64 eV), is consistent with that of chemically synthesized alkyl-capped Si NPs, 8,31,33 where emission in the ~330-360 nm region was attributed to be a result of electron-hole recombination across the direct Γ 4 eV). 17,23,37,38 The PL of the separated Si NPs, centred at 335 nm (3.64 eV), is consistent with that of chemically synthesized alkyl-capped Si NPs, 8,31,33 where emission in the ~330-360 nm region was attributed to be a result of electron-hole recombination across the direct Γ 4 eV).…”
Section: Resultssupporting
confidence: 62%
“…1c) is significantly different from the as-ablated Si NPs (Fig. 17,23,37,38 The PL of the separated Si NPs, centred at 335 nm (3.64 eV), is consistent with that of chemically synthesized alkyl-capped Si NPs, 8,31,33 where emission in the ~330-360 nm region was attributed to be a result of electron-hole recombination across the direct Γ 4 eV). 17,23,37,38 The PL of the separated Si NPs, centred at 335 nm (3.64 eV), is consistent with that of chemically synthesized alkyl-capped Si NPs, 8,31,33 where emission in the ~330-360 nm region was attributed to be a result of electron-hole recombination across the direct Γ 4 eV).…”
Section: Resultssupporting
confidence: 62%
“…The TEM image and size distribution of SiNCs suspension prepared in the DMSO have been reported in Ref. [15]. Average SiNCs radius is found to be about 1.9 ± 0.8 nm and 3.5 ± 1.5 nm in the water and DMSO respectively.…”
Section: Resultsmentioning
confidence: 89%
“…The detail of the experimental procedure has been given in reference [15]. The volume fractions of the prepared SiNC colloids in the water and DMSO were 9.0 × 10 −6 and 8.2 × 10 −6 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It was demonstrated that SiNCs produced in deionized water were much smaller when compared to the ones in polymer (Švrček and Kondo 2009). Mansour et al produced SiNCs with average size 3.5 nm by PLAL by using dimethyl sulfoxide (DMSO) as the liquid medium (Mansour et al 2012). These studies indicate that the liquid medium is quite important for the size of SiNCs, and the other suitable solvents for the production of SiNCs should be investigated in detail.…”
Section: Liquid Environment Effectmentioning
confidence: 99%
“…SiNCs are produced in the liquid environment by laser ablation. The silicon volume fraction, ϕ V inside the liquid that is ablated inside is calculated by following Equation (9.3) (Mansour et al 2012):…”
Section: Liquid Environment Effectmentioning
confidence: 99%